The mediating role of insomnia symptoms in the association between perceived neighborhood danger and depressive symptoms in later life - Seo-Yun Choi; Yuri Jang (PLoS ONE, 2026)
Perceived neighborhood danger poses significant risks to mental health in later life, yet the underlying psychological mechanisms remain unclear. Given that environmental stressors can compromise sleep health, we conceptualize insomnia symptoms as a potential mediator in the association between perceived neighborhood danger and depressive symptoms. Data from 2,240 adults aged 65 or older from Wave 3 of the National Social Life, Health, and Aging Project (NSHAP) were analyzed. Multivariate analyses showed significant associations of both perceived neighborhood danger and insomnia symptoms with depressive symptoms after controlling for sociodemographic and health covariates. Bootstrap mediation analysis provided supportive evidence for the indirect effect of perceived neighborhood danger on depressive symptoms through insomnia symptoms (B = .04, SE = .01, bias-corrected 95% CI = [.02, .07]), accounting for 25.8% of the total effect. Insomnia symptoms were identified as an important pathway through which perceived neighborhood danger undermines mental health in older adults.